Knowledge, Attitude, and Practice of Health Care Workers in Management of Bio-Medical Waste – A Cross-Sectional Study - Priyanka Sharma; Rachana Raina; Shweta Purbi; Shashi Sudhan Sharma (Universitas Ahmad Dahlan, 2022)
Background: Management of Bio-Medical Waste involves a great concern. Therefore, awareness of Health-Care Workers (HCWs) becomes very important as improper management leads to injuries and the spread of infection to the staff, patients, and environment. The objective is to assess the Knowledge, Attitude, and Practice (KAP) among Health Care Professionals regarding Bio-Medical Waste Management (BMWM). Method: This cross-sectional survey was conducted among HCWs at GMC Jammu, India. Study participants were divided into III groups (Group I- 32 Doctors, group II- 48 Paramedical staff including nurses & laboratory technicians, and group III- 20 sanitary workers). Data was collected using a pre-designed questionnaire regarding BMWM and scored as good, average, and poor. Results: In our study, knowledge regarding symbols of BMWM and awareness regarding categories and segregation of BMW was good in I and II groups but averaged in group III. None in group III has attended CME regarding BMWM in the past. In contrast, this percentage was 61% in group II and 31% in group I. Regarding the capping and destroying of needles, 88% of Paramedics were doing it correctly. None of the class IV employees received the booster dose of HBV vaccination. Conclusion: Knowledge regarding BMWM was average in Group I and Group II, whereas Group III had the slightest knowledge. Attitude regarding the BMW was good in the case of groups I and II, Whereas Group III scored average. Practices were scored average in Group I, good in Group II, and poor in group III.